1974
DOI: 10.1080/00288330.1974.9515512
|View full text |Cite
|
Sign up to set email alerts
|

Self‐purification of small freshwater streams: Phosphate, Nitrate, and Ammonia removal

Abstract: Uptake of stream nutrients by organisms or sediments of the stream bed is affected by the nutrient loading to which the stream is accustomed. In a stream with nutrient-poor waters, added phosphate and ammonia were removed rapidly and efficiently at water temperatures within the range 4.5-15.0°c on passing over a mat of filamentous algae and trapped sediment. Nitrate was removed less efficiently or not at all. In another stream where nutrients were abundant, phosphate and nitrate from a sewage outfall were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 4 publications
3
34
1
3
Order By: Relevance
“…I suspect that these high levels were due to the presence of large amounts of particulate phosphorus, which is normally an important constituent of total phosphorus (Table 6). At the time, very high suspended sediment levels were recorded (Table 4), and it is known that eroded soil and suspended sediment can contain large amounts of phosphorus (Syers 1974, McColl 1975. Additional evidence was obtained from Upper Gilbert Creek, which had both low total phosphorus (27 mg.m-3 ) and low suspended sediment levels at the time (Table 4).…”
Section: Water Chemistrymentioning
confidence: 88%
See 2 more Smart Citations
“…I suspect that these high levels were due to the presence of large amounts of particulate phosphorus, which is normally an important constituent of total phosphorus (Table 6). At the time, very high suspended sediment levels were recorded (Table 4), and it is known that eroded soil and suspended sediment can contain large amounts of phosphorus (Syers 1974, McColl 1975. Additional evidence was obtained from Upper Gilbert Creek, which had both low total phosphorus (27 mg.m-3 ) and low suspended sediment levels at the time (Table 4).…”
Section: Water Chemistrymentioning
confidence: 88%
“…For example, studies in the White Mountains of New Hampshire showed that clearfelling operations caused major increases in NO 3 -N, Ca, and K concentrations and decreases in SO 4 concentrations (Pierce et al 1972), whereas other studies have found that logging operations have diverse, but generally smaller, influences on water chemistry (e.g., Kopperdahl et al 1971, Fredricksen 1971, Verry 1972, Aubertin & Patric 1974. In New Zealand relatively little information is available on either the normal chemical composition of forest streams (see Claridge 1970, 1975a, b, White 1972, McColl 1974, Fish 1975 or the effects of logging operations Long Gully, the forested control stream, contained slightly acidic water (pH 6.5-6.9) and low concentrations of dissolved solids (mean conductivity 27/xS.cm-1 ; Table 5). The major cations present were Na (mean 3.3 g.m-…”
Section: Water Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses are in terms of sub-catchment areas because of the large river distance between sites over which streambed processes could severely alter concentrations of nutrients (e.g., McColl 1974;Rutherford et al 1987) and the large inflow of tributary waters.…”
Section: Land Usementioning
confidence: 99%
“…탈질소화는 하천 내에서 일차생산에 이용 되는 질소 영양염(Reactive nitrogen)을 완전히 제거하기 때문에 탈질소화에 의한 질소 영양염 제거는 하구에서 일차생산을 조절할 수 있다 (Groffman and Crawford, 2003;Royer et al, 2004;Mulholland et al, 2008) 하구는 얕은 수심으로 인해 일차생산에 의해 생긴 유기물이 대부분 하구 퇴적물로 침강한다. 그러므로 하구에서는 수층뿐 만 아니라 퇴적층 또한 영양염 순환에 중요한 역할을 한다 (McColl, 1974;Cowan et al, 1996;Herbert, 1999;정과 조, 2003;Utlay et al, 2008). 수층에서 일차 생산에 의해 형성된 유기물의 약 50%가 퇴적층에서 분해되며, 퇴적층에서 재생산된 영양염 의 0-80%가 식물플랑크톤 생산에 쓰인다 (Cowan et al, 1996).…”
Section: 암모늄과 같은 용존 무기질소의 경우 광합성 및 호흡에 의해 제거 및 공급되며 더불어 질산화 과정 및 탈질소화unclassified